Chinese and Global ADRs: The US Investor Experience. Issue 3 (3rd July 2021) - Bessembinder, Hendrik; Chen, Te-Feng; Choi, Goeun; Wei, K. C. John
Abstract : We study outcomes to ADR (American Depositary Receipt) investments between August 1954 and September 2020, with particular attention to ADRs associated with Chinese firms. Overall, ADRs improved investors' wealth by 1.03 trillion, with more than a third of this amount attributable to ADRs associated with Chinese firms. A value-weighted portfolio of ADRs associated with Chinese firms earned 14.1% per year since the first Chinese ADR was created in 1993, as compared with 9.9% per year for the overall US stock market over the same period. These data are relevant to current policy discussions focused on Chinese firms listed in the United States.